The Importance of Community: Planning a Reparative Description Symposium in Your State - Smeltekop, Nicole (My University, 2025)
On April 1, 2025, MSU Libraries hosted the Symposium on Reparative Description in Library Catalogs. This event was attended by 80 cultural heritage workers from across the state and beyond (including Ohio, Indiana, and Canada!) and from a range of institutional types such as academic, community college, public, government, archives, K-12 school, library school students, faculty, and vendors. With no experience running a symposium (but plenty of enthusiasm!), the planning team was thrilled with the response of our colleagues across the state and types of institutions! This presentation will walk through our process of building the symposium from scratch, including assembling the planning team, building the program, and soliciting sponsorships, all while holding our values of inclusivity for all (by keeping costs minimal for attendees) and centering our Indigenous colleagues’ voices and perspectives for the day.
Keywords: Archives; Metadata; Academic library; Public library; Tribal library; Museum